Analisis Penyebab Pengembalian Klaim BPJS Pasien Rawat Inap Ditinjau Dari Proses Pengkodean Di RSUD Majenang - Zahra, Awlia Varasemitha; Hakim, Agya Osadawedya; Fauzi, Harry; Gunawan, Gunawan (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Pending Claim is a refund because there is no agreement between BPJS Health and FKRTL regarding coding rules and medical determination (claim dispute). The correct diagnosis and action code will determine the smooth process of submitting claims for medical services to BPJS Health and reduce the number of claim returns. This study aims to determine the causes of inpatient claim returns in terms of the coding process at Majenang Hospital. The research method used is a qualitative method with an observational descriptive design. Data was obtained from pending claims from July to September 2023. Data collection methods were observation and interviews. Majenang Hospital research results showed that 371 claims were returned and 187 claims were returned due to coding confirmation. Factors inhibiting the accuracy of a diagnosis or action code are the use of combined codes, errors in determining the main diagnosis, differences in perception, and discrepancies in supporting results with the diagnosis. Efforts that can be made to minimize the number of claim returns include reviewing diagnosis or action codes, communicating between DPJP, the casemix team and BPJS verifiers, coding training and having an SPO.